Advances in the Diagnosis, Treatment, and Prognosis of Chronic Kidney Disease: A Reflection on Recent Developments - Cindy George; Andre Pascal Kengne (Applied Sciences, 2024)
Chronic kidney disease (CKD) remains a critical global health issue, affecting more than 840 million individuals globally [...]